Analysis of Student Transportation Needs at Universitas Gadjah Mada - Kusuma, Rifda Galuh; Rachmawati, Rini (Universitas Indonesia, 2020)
Universitas Gadjah Mada (UGM) in Indonesia brings thousands of new students annually. This greatly affects the use of transportation modes and the need for modes of transportation to the campus. This study aims to determine the modes of transportation used by students to campus, factors that influence the choice of transportation modes, and the needs of student transportation modes. This study uses a quantitative approach with descriptive analysis and Cramer's V correlation test. The results of the study show that the transportation modes used by Universitas Gadjah Mada’s students as a means of transportation to the campus are mostly private (70.5%). Factors that influence the choice of modes of transportation are private vehicle ownership, driving license ownership, monthly allowance, residence, frequency of use of transportation modes, time of movement, distance traveled, transportation modes changing, travel time, transportation costs, security/safety, timeliness, and speed. The modes of transportation needed by students are motorbikes and online transportation/ride-hailing service. The transportation characteristics that are most needed by students are fast, cheap, and comfortable. As many as 89.4% of students agreed and as many as 10.6% of students did not agree if there were vehicles provided by the campus.